UPAYA PENINGKATAN PROFESIONALISME GURU SMP IT AL AZHAR BOARDING SCHOOL BALIKPAPAN KALIMANTAN TIMUR - jurnalpps pps; M. Abdurachman Rochimi; Woro Utari (Prodi Magister Manajemen Universitas Wijaya Putra, 2021)
This study was to determine the professionalism of teachers and work culture and teacher performance at SMP IT Al Azhar Boarding School. It also aims to find out the school's efforts in improving the professionalism of SMP IT Al Azhar Boarding School teachers and to find out the supporting and inhibiting factors in increasing the professionalism of SMP IT Al Azhar Boarding School teachers. In this study there were 29 people as informants consisting of the Principal, Deputy Principal and all teachers of SMP IT Al Azhar Boarding School. This research was conducted at SMP IT AL Azhar Pondok Pesantren Balikpapan, East Kalimantan. The results of this study indicate that there are several supporting and inhibiting factors in efforts to increase teacher professionalism at SMP IT AL Azhar Balikpapan, all of which are part of the process towards an advanced school.